DEVELOPMENT OF CHEMISTRY TEACHING MODULE BASED ON DIFFERENTIATION LEARNING TO IMPROVE STUDENT LEARNING OUTCOMES ON ATOMIC STRUCTURE MATERIAL - Hartati, Ajeng; Wijayanti, Imas Eva; Solfarina (UIN Mataram, 2024)
Atomic structure material is relatively complex and abstract material so it requires in-depth understanding and good visualization so that it is easy for students to understand. Differences in students' initial understanding and learning styles are the trigger for low student learning outcomes in atomic structure material. The solution is to apply differentiated learning. This research aims to develop a chemistry teaching module based on differentiated learning that can improve student learning outcomes in atomic structure material, especially in electron configuration material and the periodic system of elements. This development research uses the ADDIE model. The results of the research show that the chemistry teaching module based on differentiated learning in atomic structure material obtained a very feasible category in the material field with a percentage of 89.76% and obtained a very feasible category in the media field with a percentage of 88.59%. The chemistry teaching module based on differentiated learning is effective in improving student learning outcomes as shown by the acquisition of the Wilcoxon test, namely the Asymp.Sig value. (2-tailed) is 0.000. The results of students' responses to the chemistry teaching module based on differentiated learning on atomic structure material obtained an average percentage of 82.38% in the very good category, so that the chemistry teaching module based on differentiated learning on atomic structure material is suitable for use as a learning medium that can help participants. students to improve their learning outcomes.